Preparation of iron oxide (Fe2O3) nanoparticles thin film for humidity sensing device - Korakot Onlaor; Ukit Boontanom; Thutiyaporn Thiwawong; Potiyan Songkeaw; Benchapol Tunhoo (My University, 2021)
In this work, the iron oxide (Fe2O3) nanoparticles thin films were applied to prepare humidity device. Fe2O3 nanoparticles were prepared by precipitation process following with post sintering process at various temperatures. The properties of Fe2O3 nanoparticles were characterized by X-ray diffraction, Raman spectroscopy, and Fourier transform infrared spectroscopy, respectively. The effect of sintering temperatures on properties of synthesized particles was investigated. To fabricate the humidity device, the suspension of Fe2O3 nanoparticles in ethanol solvent was dropped on gold interdigited electrodes. The device impedance demonstrated the response of humidity level at various values. The humidity sensing characteristics such as sensitivity, response times, and hysteresis, respectively, were performed. It was observed that the humidity response depended on the post sintering temperatures of Fe2O3 nanoparticles.
Keywords: Iron oxide nanoparticles; Gas Sensing Nanomaterials and Sensors